O devir do conceito de meio entre os séculos XVII e XIX, segundo a História das Ciências de Georges Canguilhem - Medeiros, Claudio V. F. (2014)
This work aimed to make an analytical experience of Georges Canguilhem s historiography of science, guided by some findings obtained by him in the article Le Vivant et son Milieu (1946-1947). Such article narrates the history of a scientific concept, in other words, the historical composition of the variations of use and meaning which characterize the concept of milieu. This concept inaugurated along its overturns and deviations between the XVII and XIX centuries the possibility of elucidation of an organic reaction by the action of a milieu. In consequence, it s important to elucidate not only the historical fecundity of the concept, but the relationships between the milieu, understood as a historically new category of reasoning, and the individuality of the living being. In the consecution of this research, the initial axis of Canguilhem s narrative will be adopted, which follows the sequence of five works: Principles of Philosophy (1644), by Descartes; Mathematical Principles of Natural Philosophy (1686) and Opticks (1704), by Newton; Histoire Naturelle, générale et particulière (1749-1788), by Buffon and Philosophie Zoologique (1809), by Lamarck. The analysis will be concentrated in the first discontinuities of the concept. In Le Vivant et son Milieu , Canguilhem stretches the frame of his analysis until mid-twentieth. Such deployments of the concept, which go further the XIX century, will not appear in the analysis of this research